Dominance of Saudi Arabia in the Middle East after the Arab Spring - Mohd Jody, Jeniwaty (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
This article seeks to utilize double track diplomacy to examine Saudi Arabia's foreign policy following the Arab uprisings, with a focus on Saudi dominance in the Middle East. The research aims to illustrate a transition in Saudi Arabia's foreign policy from a strategy of balancing to one of leadership and coalition-building, as framed by the balance of threat theory. The central inquiry is: what effect did the altered security environment of the Middle East post-2011 Arab uprisings have on Saudi foreign policy? Addressing this question, and considering the assertion that the nature of threats in the Middle East has shifted post-uprisings in a way that directly threatens the stability of the Saudi regime, necessitating a different response, our hypothesis posits that Saudi foreign policy moved from traditional balancing (aligning with international powers against threats) to a more independent and self-reliant stance.             However, Saudi Arabia's assertive stance towards Yemen, Bahrain, and Syria in reaction to regional events has led to heightened fear and instability in the region. These actions have the potential to shift the balance of power, posing significant challenges to the legitimacy of these nations within their respective spheres of influence.